Bleeding and Thrombotic Adverse Events in Hospitalized Patients Under Empiric Treatment for Suspected Heparin-Induced Thrombocytopenia While Awaiting Confirmatory Testing - Dykes, Kaitlyn C. (Clin Appl Thromb Hemost, 2021)
Empiric management in suspected heparin-induced thrombocytopenia (HIT) is challenging due to imperfect prediction models, latency while awaiting test results and risks of empiric therapies. When there is high clinical suspicion for HIT, cessation of heparin and empiric non-heparin anticoagulation with FDA-approved argatroban is recommended. Alternatively off-label fondaparinux or watchful waiting have been utilized in clinical practice. Outcomes of patients empirically managed for HIT have not been compared directly in clinical trials and patients that ultimately do not have HIT are often overlooked. Clinicians need studies investigating empiric management to guide decision making in suspected HIT. In this study, adverse events (AE) were categorized and compared in patients being evaluated for HIT while undergoing empiric management by non-heparin anticoagulation with argatroban or fondaparinux, both at therapeutic or reduced doses, or watchful waiting with or without heparin. AE were defined as new thrombosis confirmed on imaging or new bleeding event after HIT was first suspected. A retrospective chart review of 312 patients tested for HIT at an academic hospital was conducted. 170 patients met inclusion criteria. Patients were excluded if the 4Ts score was < 4. The 4Ts score is a pretest probability for HIT based on thrombocytopenia degree, timing, alternative causes and presence of thrombosis. Included patients were divided according to management groups and compared with logistic regression analysis. Bleeding risk significantly differed between management groups (p = 0.002). Despite adjustment for bleeding risk, fondaparinux was associated with increased AE, (p = 0.03, OR = 5.81), while argatroban was not. There was no difference in AE based on time to initiation of empiric treatment and no advantage to reduced dosing with either anticoagulant. These findings challenge assumptions surrounding empiric HIT management.